2001
DOI: 10.1046/j.1460-9592.2001.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble P‐selectin and the postoperative course following cardiopulmonary bypass in children

Abstract: A relation between CPB-induced mediators and both early and late clinical effects is suggested. The up-regulation and expression of sP-selectin indicate neutrophil activation as a possible mechanism for the increase, and inhibiting it may reduce the inflammatory response associated with CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…10,11 Recently, sP-selectin levels were found to correlate with increased postoperative mortality risk score, hypotension, and tachycardia in children undergoing CPB. 12 However, our data show no relationship between sP-selectin levels and the clinical data. The sP-selectin levels rose postoperatively and a significant increase was detected even 20 hours after CPB, but no difference was found between sP-selectin levels in patients who needed norepinephrine in the ICU and the control patients.…”
Section: Discussioncontrasting
confidence: 71%
“…10,11 Recently, sP-selectin levels were found to correlate with increased postoperative mortality risk score, hypotension, and tachycardia in children undergoing CPB. 12 However, our data show no relationship between sP-selectin levels and the clinical data. The sP-selectin levels rose postoperatively and a significant increase was detected even 20 hours after CPB, but no difference was found between sP-selectin levels in patients who needed norepinephrine in the ICU and the control patients.…”
Section: Discussioncontrasting
confidence: 71%
“…It was found that sP-selectin levels correlated with the postoperative "pediatric risk of mortality"-score, hypotension and tachycardia in children undergoing CPB (16). In agreement with previous studies (17,18), sP-selectin increased after CABG in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Most earlier works which had studied inflammatory indices after CPB measured these mediators only in the acute postoperative period (1–5). We recently conducted an investigation in which we monitored plasma soluble P‐selectin in paediatric patients who had a complicated course following CPB, and our results suggested that it might be used as a marker to predict the postoperative course (14). Our current study had a twofold purpose: to look for a possible association between IL‐8 levels with morbidity and mortality during the early postoperative course in infants or children after undergoing CPB and to compare IL‐8 levels in those children who had a complicated course immediately postoperatively to those whose course was unremarkable.…”
Section: Discussionmentioning
confidence: 99%